Feasibility of Repurposing the Polyanionic Microbicide, PPCM, for Prophylaxis against HIV Transmission during ART. (28th November 2010) - Anderson, Robert A.; Brown, David; Jackson, Erin M.; Feathergill, Kenneth A.; Bremer, James W.; Morack, Ralph; Rawlins, Richard G.
Abstract : HIV-serodiscordant couples wishing to conceive often seek assisted reproduction, during which spermatozoa from infected men are washed to minimize the risk of HIV transmission to partner and fetus. We sought to improve this method by adding a microbicide, PPCM, as an HIV prophylactic. HIV-1 (BaL) inhibition by PPCM appears irreversible and independent of added Ca 2+ . Without added Ca 2+, PPCM (≤10 mg/mL, ≤90 min), a stimulus of Ca 2+ -dependent acrosomal loss, has no effect on sperm motility, forward progression, or acrosomal status. PPCM-treated (10 mg/mL) sperm retain their ability to acrosome react when Ca 2+ is added. Sperm DNA integrity/function is unaffected by PPCM (≤10 mg/mL). Adding PPCM (5 mg/mL, 30 min) to washing media reduces infectivity (viral antigen p24 and RNA) of ex-vivo HIV-infected semen by 3-4 Logs compared with washing alone. Sperm washing with appropriate extracellular Ca 2+ levels and PPCM is significantly more effective than washing alone at reducing HIV infectivity.